صور الانحراف في المخيال الاجتما عي دراسة تحليلية على عينة من الأمثال الشعبية الجزائرية - بوشكارة سليمة ياسمين; اشراف عزوز عبد الناصر (جامعة المسيلة كلية العلوم الانسانية والاجتماعية, 2026)
This study aims to uncover and clarify the deviant images held by the social imaginary by analyzing Algerian popular proverbs. These proverbs are considered a cultural reference reflecting the popular culture of society, especially those that implicitly express culturally justified and socially accepted deviant behaviors. Thus, the study sought to understand how deviant behaviors are granted legitimacy for practice through popular proverbs concerned with deviance in general. This stems from the meanings individuals ascribe to these proverbs, making them a source of social interaction from which individuals draw and see themselves through their embodiment, as they are the product of prior experiences and knowledge of previous generations. To extract the deviant images within popular proverbs, thereby enabling us to understand the nature of the imaginary in the realm of deviance, the content analysis methodology was employed. This involved analyzing the content of a purposive sample represented by proverbs carrying an image or connotation indicative of deviance. The sample consisted of 200 proverbs out of a total population of 360 popular proverbs. This analysis was conducted to answer the question regarding the nature of deviant images within the Algerian social imaginary.